(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
The field of social studies education is rooted in citizenship education. With this in mind, social studies teachers should implement to the best of their capabilities a “democratic classroom” as an incubator and laboratory in which students can learn about, practice, and build values as democratic citizens. To do this, teachers should work with students to design and operate within democratic classroom structures, encourage discussion and deliberation, foster self-trust and mutuality, and engage in critical analysis.